Michał Heller, Jak być uczonym, Społeczny Instytut Wydawniczy Znak, Kraków 2009, ss. 72. - Bogusiewicz, Kinga (Poznańskie Studia Teologiczne, 2015)
Michał Heller, Jak być uczonym, Społeczny Instytut Wydawniczy Znak, Kraków 2009, ss. 72.